Strategies for Developing Holistic-Integrative Programs in Early Childhood Education - Muji Agus Sofiyandi; Syamsul Arifin; Inshomuddin; Tobroni (Journal of Educational Studies, 2025)
This study addresses the limited provision of early childhood education (ECE) services, which remains disproportionate to the number of children requiring access. Existing programs, such as toddler family development initiatives and integrated health service posts, have not yet delivered comprehensive, synergistic, and integrative services encompassing education, health, and nutrition. Therefore, this research aims to examine the implementation strategy of holistic-integrative early childhood education at the As-Syifa Early Childhood Education Center in Orong Bawa Village, Utan District. Data were collected through interviews, questionnaires, observations, and documentation, and analyzed using SWOT analysis to identify internal (strengths and weaknesses) and external (opportunities and threats) factors influencing the Holistic-Integrative ECE (PAUD HI) program. The results show an internal factor score of -0.2 and an external factor score of 0.6, positioning the program within a specific SWOT quadrant that informs strategic development. The findings indicate that the development of holistic-integrative ECE can be achieved through: (1) the provision of holistic services covering education, health, and child guidance; (2) the implementation of integrative learning strategies addressing cognitive, affective, and psychomotor domains; and (3) strengthening communication and guidance for parents. Furthermore, effective coordination with related institutions, such as integrated health service posts (Posyandu) and Bina Keluarga Balita (BKB), is essential. In conclusion, holistic-integrative ECE plays a critical role in facilitating comprehensive child development and requires collaborative, systematic, and integrated implementation among all stakeholders.